2003
DOI: 10.1093/occmed/kqg077
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of measles susceptibility among health care workers in a UK hospital. Does the UK need to introduce a measles policy for its health care workers?

Abstract: The prevalence of measles non-immune health care workers is low, but with a fall in uptake of MMR immunization and increased likelihood of measles outbreaks, it is important to identify these at-risk individuals. Serum testing is the most reliable method to use. Oral fluid testing and history of measles disease or vaccination are unreliable methods of identifying non-immune individuals. To achieve complete immunity, it is cost-effective to screen and then offer immunization. NHS trusts vary greatly in their me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
13
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 14 publications
5
13
0
3
Order By: Relevance
“…We recorded a poor correlation between each individual's antibody levels and the history of vaccinations, which is consistent with previous findings [29]. It is clear that better mechanisms for recording individual immunizations should thus be developed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We recorded a poor correlation between each individual's antibody levels and the history of vaccinations, which is consistent with previous findings [29]. It is clear that better mechanisms for recording individual immunizations should thus be developed.…”
Section: Discussionsupporting
confidence: 89%
“…Individuals lacking measles and rubella antibodies were only seen in the youngest age cohorts, most likely due to waning immunity years after vaccination in individuals lacking contact with the wild virus [24,27,28]. Other studies have also shown the tendency of non-immune individuals to be seen in younger age groups [8,29]. This is concerning, since especially fertile individuals should be protected against rubella to avoid the risk of congenital rubella syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In HCWs, including medical students, seropositivity for measles, mumps and rubella ranges from 84% to 98.5% [20][21][22][23][24][25][26]. This variation in immunity is due to differences in vaccination coverage and intensive circulation of wild type virus in some areas.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of measles in non-immune health care workers is low, but with a fall in the uptake of MMR immunization and the increased likelihood of measles outbreaks, it is important to identify these at-risk individuals. To achieve complete immunity, it is costeffective to screen and then offer immunization 16) as the World Health Organization states: "in some settings, medical personnel have been the source of measles spread. Policies requiring immunization or proof of immunization may need to be implemented" 17) .…”
Section: Discussionmentioning
confidence: 99%